Īśvarapratyabhijñāvivrtivimarśinī - Abhinavagupta, Rājānaka (Kaśmīrasaṃskrtagranthāvaliḥ, 1938)
Commentary, with text, on Īśvarapratyabhijñā, classical verse work expounding the Trika philosophy in Kashmir Sivaism, by Utpala, fl. 900-950.